Mitochondrial dysfunction and mitochondrial DNA mutations in atherosclerotic complications in diabetes - Chistiakov, Dimitry A (Baishideng Publishing Group Co., Limited, 2012)
Mitochondrial DNA (mtDNA) is particularly prone to oxidation due to the lack of histones and a deficient mismatch repair system. This explains an increased mutation rate of mtDNA that results in heteroplasmy, e.g., the coexistence of the mutant and wild-type mtDNA molecules within the same mitochondrion. In diabetes mellitus, glycotoxicity, advanced oxidative stress, collagen cross-linking, and accumulation of lipid peroxides in foam macrophage cells and arterial wall cells may significantly decrease the mutation threshold required for mitochondrial dysfunction, which in turn further contributes to the oxidative damage of the diabetic vascular wall, endothelial dysfunction, and atherosclerosis.